Pengembangan media V-Poldynamics untuk pembelajaran geografi materi antroposfer - Muhammad Zainul Muttaqin; Sumarmi Sumarmi; Ifan Deffinika (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
Nowadays this learning is highly demanded for media literacy and utilizing technology in learning. Teachers must be able to adapt and utilize technology for an effective learning process. The development of V-Poldynamics learning media was carried out, there were deficiencies in the use of media during the direct learning process, especially material regarding population quality, human development index and demographic bonus. This research aims to produce video products and the feasibility of V-Poldynamics media in learning. The development research model uses the ADDIE method (Analyze, Design, Development, Implementation, Evaluation). This research data uses 2 data, namely qualitative and quantitative data. Qualitative data was generated from media experts and material experts. Quantitative data can be obtained from teachers and students from the distribution of criticism, suggestions and responses questionnaires. The results of the material expert validation stage which consists of 5 aspects of the assessment get an average value of 95 percent which indicates that this material is very feasible to use in making the product. The results of the media expert validation stage which consists of 6 aspects of the assessment get an average value of 96 percent which indicates that this media is very feasible to use in learning. Product trial activities were carried out in class XI IPS three MA Al-Ittihad. The results of this product trial received an average percentage value of 95 percent from the assessment of the material aspect, 96 percent of the results from the media aspect, and 89 percent came from the average assessment of teachers and students. The V-Poldynamics learning media is very feasible and can be used in the learning process. Saat ini, guru dituntut untuk memiliki kemampuan literasi media dan penggunaan teknologi pembelajaran. Guru harus mampu menyesuaikan diri dan memanfaatkan teknologi untuk proses pembelajaran yang efektif. Pengembangan media pembelajaran V-Poldynamics dilakukan karena kurangnya pemanfaatan media saat proses pembelajaran terutama materi kualitas penduduk, indeks pembangunan manusia dan bonus demografi. Tujuan penelitian ini menghasilkan produk video dan kelayakan media V-Poldynamics dalam pembelajaran. Model penelitian pengembangan menggunakan metode ADDIE (Analyze, Design, Development, Implementation, Evaluation). Data penelitian ini memakai 2 data yaitu data kualitatif serta kuantitatif. Data kualitatif dihasilkan dari para pakar media dan pakar materi. Data kuantitatif diperoleh dari guru dan peserta didik melalui persebaran angket kritik, saran dan tanggapan. Hasil dari tahap validasi pakar materi yang terdiri dari 5 aspek penilaian mendapat nilai rata-rata 95 persen, menunjukkan bahwa materi ini sangat layak digunakan dalam pembuatan produk tersebut. Hasil dari tahap validasi pakar media yang terdiri dari 6 aspek penilaian mendapat nilai rata-rata 96 persen, menunjukkan bahwa media ini sangat layak digunakan dalam pembelajaran. Kegiatan uji coba produk dilakukan di kelas XI IPS tiga MA Al-Ittihad. Dari hasil uji coba tersebut, penilaian aspek materi mendapat nilai rata-rata 95 persen, 96 persen dari aspek media, dan penilaian rata-rata penilaian guru dan peserta didik sebesar 89 persen. Media pembelajaran V-Poldynamics tersebut dapat dikatakan sangat layak serta bisa dipergunakan pada proses pembelajaran.